Influence of competitive match play on countermovement jump performance, lower-limb isometric strength, and self-reported subjective measures 40 hours postmatch in professional soccer - Mukandi, I.; Bishop, C.; Turner, A.; Beato, M. (The Journal of Strength and Conditioning Research, 2026)
This study investigated the impact of competitive match play on countermovement jump (CMJ) performance, hamstrings and adductor isometric strength, and subjective self-reported measures 40 hours postcompetitive match play in professional soccer players. Twenty-eight professional players completed baseline assessments during preseason. Assessment 40 hours postmatch was limited to players who played >=60 minutes, with players grouped into 2 categories based on minutes played: 60-89 minutes or 90-110 minutes. Baseline measures for subjective self-reported measures were collected 24 hours before each match. Across both groups, significant reductions (p < 0.05) were observed in all outcome, ratio, and driver metrics except for eccentric mean force. All strategy metrics significantly increased (p < 0.05). Minutes played and match demands were not significantly associated with CMJ performance (tb = -0.07 to 0.16 and tb = -0.28 to 0.00, respectively). Prone isometric 0° showed nonsignificant reductions (p > 0.05) in both conditions with trivial to small effects. Significant reductions (p < 0.05) were observed for both conditions for the supine 90° hamstring test, however minutes played, and match demands were not significantly associated with a reduction in performance (tb = -0.04 to -0.01 and tb = -0.27 to 0.21). Short lever hip adduction results showed nonsignificant reductions (p > 0.05) in the 60-89 minutes group, but significant decreases (p < 0.001) were observed for the dominant limb, nondominant limb, and total score in the 90-110 minutes condition. However, minutes played and match demands were not significantly associated with reduction in adductor isometric strength (tb = 0.18-0.22 and tb = -0.15 to 0.11). Subjective measures revealed significant reductions in sleep quality (p < 0.05) and composite scores (p < 0.001), and significant increases in muscle soreness (p < 0.001) across both conditions. Mood was only significantly reduced (p < 0.05) in the 90-110 minutes condition. No significant associations were found between minutes played, match demand, and self-reported subjective scores (tb = -0.07 to 0.05 and tb = -0.09 to 0.00).